Design and Production of Multimedia and Simulation-based Learning Material
XVI, 253 p.
Keywords: This volume results from a meeting that was held in Barcelona, Spain, April 1993, under the auspices of the DELTA programme of the European Commission. DELTA (Developing European Learning through Technological Advance) is the commission's technology R&D programme that concentrates on "Telematic Systems for Flexible and Distance Learning". The overarching goal of this programme is to contribute through information technology to more efficient and effective design, production, and delivery of learning material. The DELTA programme started its main phase in 1992 with a total of 22 projects and a total budget of 92. 4 million ECU. In the meanwhile an extension of the programme has resulted in 8 extensions of existing projects and 8 new projects, bringing the number of projects to 30, with a corresponding total budget of 99. 9 million ECU. The programme has three main areas: telecommunication, delivery information systems, and design and production. In the projects, in total 201 organisations (industrial, commercial, and universities) from 12 European Union member states and 5 EFTA countries are represented. The DELTA programme pays much attention to the exchange of ideas and dissemination of information both between individual DELTA projects and between DELTA projects and other initiatives in the EU. Meetings in which DELTA projects are involved are held several times a year as so-called 'concertation meetings', meetings where also non-DELTA projects participate are called 'concerted actions'.